2014
DOI: 10.1590/s0100-67622014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Banco de sementes do solo e serapilheira acumulada em floresta restaurada

Abstract: RESUMO -Este estudo teve por objetivo avaliar o banco de sementes do solo e a serapilheira acumulada em uma floresta restaurada por meio de plantio, com 40 anos, em Viçosa, MG. Foram alocadas 16 parcelas contíguas de 25 x 25 m, cobrindo toda a área da floresta (1 ha). Em cada parcela, foram coletadas cinco amostras de solo superficial (0,30 x 0,30 x 0,05 m) para avaliação do banco de sementes pelo método de germinação e uma amostra de 1,0 m² de serapilheira para avaliação da serapilheira acumulada. Foi realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
2
3
0
4
Order By: Relevance
“…In total, 554 seedlings m -2 were found in a given area after six restoration years, whereas 1,056 seedlings m -2 were recorded after nine restoration years (Sorreano, 2002). Previous studies had also found 857.6 seedlings m -2 in a secondary forest in a kaolin mining area located in Minas Gerais State, Brazil (Martins et al, 2008): 771 seedlings m -2 in an area were subjected to 40 restoration years (Miranda Neto et al, 2014), 357 seedlings m -2 in an area were subjected to 23 restoration years (Correia & Martins, 2015) and, finally, 2,489 seedlings m -2 in an area restored for 10 years after being subjected to bauxite mining activity (Miranda Neto et al, 2017). The variation in soil seed density in different areas is associated with several factors such as the history of the area, propagule source and dispersing fauna (Franco et al, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…In total, 554 seedlings m -2 were found in a given area after six restoration years, whereas 1,056 seedlings m -2 were recorded after nine restoration years (Sorreano, 2002). Previous studies had also found 857.6 seedlings m -2 in a secondary forest in a kaolin mining area located in Minas Gerais State, Brazil (Martins et al, 2008): 771 seedlings m -2 in an area were subjected to 40 restoration years (Miranda Neto et al, 2014), 357 seedlings m -2 in an area were subjected to 23 restoration years (Correia & Martins, 2015) and, finally, 2,489 seedlings m -2 in an area restored for 10 years after being subjected to bauxite mining activity (Miranda Neto et al, 2017). The variation in soil seed density in different areas is associated with several factors such as the history of the area, propagule source and dispersing fauna (Franco et al, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…Other studies, in similar environments, found a reduced stock of shrub-tree species and observed a predominance of herbaceous plants (Tres et al, 2007;Pereira et al, 2010;Miranda et al, 2014). Some authors point out that the results may be influenced by the method used -germination or direct counting -due to errors associated with seed dormancy and mortality (Pereira et al, 2010;Silva et al, 2011).…”
Section: /11mentioning
confidence: 94%
“…DISCUSSION A dominance of Cyperaceae and even herbaceous non-grass plants is commonly found in seed banks of abandoned pastures or fragmented environments (Wijdeven & Kuzee, 2000;Miranda et al, 2014). Factors that contribute to this pattern include efficient dispersion mechanisms, reduced size, dormancy, and high seed production (Guimarães et al, 2014).…”
Section: /11mentioning
confidence: 99%
“…Tanto na vegetação secundária como no sistema agroflorestal foi observada a predominância de espécies herbáceas (59%) sobre as lianas (18%), arbóreas (14%) e arbustivas (9%). Resultados semelhantes foram encontrados em sistemas agroflorestais no Mato Grosso do Sul (MORESSI, et al 2014), floresta restaurada em Minas Gerais (MIRANDA NETO et al, 2014), em distintos estágios de regeneração natural em área de Caatinga na Paraíba (FERREIRA et al, 2014) e em áreas sob diferentes tipos de Caatingas manejadas no semiárido paraibano (RIBEIRO et al, 2017).…”
Section: Resultsunclassified